SISTEM INFORMASI DUGAAN SEMENTARA PENENTUAN JENIS PENYAKIT DENGAN GEJALA DEMAM MENGGUNAKAN SISTEM PAKAR BERBASIS SHORT MASSAGE SERVICE (SMS) - -, Uminingsih (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Information system to diagnose diseases with fever symptom using expert sys-tem based on SMS (source massage service). Computer is a electronic instrument which is very needed for data processing in order to provide information fast and accurately. One of the computer application is used by health expert to make a system to deliver information of diagnose disease result based on consultation data from a patient. Disea-se detection done by collection of symptom of every diseases which has a certainty factor (CF).The health information system is made using Delphi 6. Microsoft Access 2000, Mysql and SMS Gateway version 11.4. The investigation result shows that health infor-mation system can decide the same diseases different CF.This is because of source di-seases having the same symptom with an another diseases . The CF is obtained from the calculation between CF symptom and CF expert system. The access of the information is done by SMS medium with SMS Gateway connecting the computer with terminal hand phone.